A study on the fire fighting system in UiTM Shah Alam / Mohd Alfi Syahrin Ibrahim - Ibrahim, Mohd Alfi Syahrin (Faculty of Architecture, Planning and Surveying, 2013)
This dissertation completed was mainly motivated by the desire to provide a good management for fire fighting system in University Technology Mara ( Uitm ) Shah Alam. This is intended to establish a better fire fighting system planning to be adopted in the management practice of University Technology Mara ( Uitm ) Shah Alam. The study has specific aim and objectives to achieve which is the main part of the research. The primary aim of this study is to understand the management of the fire fighting system in this institutional. Meanwhile, the second objective is to identify the awareness of the occupant about the importance of fire fighting system in building and the third objective is to investigate the problem occurs for recommend a better approach in managing fire fighting system UITM Shah Alam. This dissertation includes the outlines of the introduction to the subject and each subtopic, and also explanation about fire fighting management systems in UITM Shah Alam. Research methodologies which apply are through literature review, observation, questionnaire survey to the students and staff, and interview session with mechanical engineer in facilities management department. Then, data analysis and findings are based on literature review, research method and additional outsource references. From analysis, it can be found that the management of fire fighting systems for UITM Shah Alam are moderate and the knowledge about fire fighting among student and staff are lack. Finally, conclusion and recommendation is made according to research findings. Fire fighting or maintenance management department should re-examine about step and method to accomplish this fire fighting.